HUBUNGAN TINGKAT PENGETAHUAN, SIKAP DAN MOTIVASI IBU DALAM PEMBERIAN STIMULASI DENGAN PERKEMBANGAN ANAK USIA 3-5 TAHUN DI WILAYAH RW 04 KELURAHAN KEDUNG JAYA - Windu Syawalina Wahyuningsih (Indonesian Journal of Health Development, 2021)
Children are individuals who in the range of developmental transitions and prone to developmental problems. The delay in child development is influenced by the stimulation of parents, especially a mother. This study aims to determine the relationship between the level of knowledge, attitudes and motivation of mothers in giving stimulation with the development of children aged 3-5 years in the area of ​​RW 04 Kedung Jaya Village. The method used is descriptive analytic with proportional random sampling technique as many as 83 mothers with children aged 3-5 years. Univariate analysis using proportion test and bivariate analysis using Chi-Square test. The results of this study indicate that there is a significant relationship between the mother's level of knowledge in giving stimulation with child development, p-value = 0.000, there is a significant relationship between mother's attitude in giving stimulation with child development, p-value = 0.000, and there is a significant relationship between the mother's motivation in giving stimulation with the child's development, p value = 0.000. In this research, mothers are expected to participate in training and socialization about stimulation in order to understand the correct and appropriate stimulation. Mothers should follow the child's developmental screening on a regular basis.